FORMING AN ACTIVE, CULTURED, AND COMPETITIVE GENERATION WITH TRADITIONAL GAME APPROACHES IN PHYSICAL EDUCATION LEARNING: MEMBENTUK GENERASI AKTIF, BERBUDAYA, DAN BERDAYA SAING DENGAN PENDEKATAN PERMAINAN TRADISIONAL PADA PEMBELAJARAN PENDIDIKAN JASMANI - Olivia Dwi Cahyani, Olivia (UPMI Proceeding Series, 2023)
Physical education is an important aspect in forming an active, healthy and competitive generation. Traditional games have cultural value, social values, and physical benefits that are important for children's development. The purpose of this study is to explore the effectiveness of the traditional game approach in learning physical education in forming an active, cultured, and competitive generation in the era of globalization. This study will analyze the impact of this approach on motor skills, improved cultural understanding, and children's social and emotional development. Research methods using qualitative methods through thematic analysis methods, data from observations and interviews will be analyzed to gain a deep understanding of the benefits and contributions of traditional games in the context of Physical Education Learning. Triangulation of data will also be conducted to strengthen the validity of the findings. The results of observations and interviews with thirty respondents, obtained results with high categories where traditional games contribute to developing motor skills, enrich cultural understanding, improve social interaction, and stimulate creativity. Conclusion the traditional game approach in learning Physical Education has significant potential in shaping an active, cultured, and competitive generation in the era of globalization. Traditional games have important cultural value and are able to enrich children's understanding of their cultural heritage. In addition, traditional games can also improve motor skills, promote positive social interactions, and provide a good emotional response in children. By involving traditional games in learning, an active, creative, and fun environment can be created for children to learn.